Environmental and lifestyle factors increasing ALS susceptibility - Visser, A.E. (Utrecht University, 2019)
Amyotrophic lateral sclerosis (ALS) leads to muscle weakness due to degeneration of motor neurons. On average, patients die about three years after their first symptoms. Up till now the exact disease mechanism has not been clarified and therefore there is no lifesaving treatment. To gain more knowledge about possible mechanisms, we examined environmental and lifestyle factors as risk factors for ALS in a population-based, case-control study. In collaboration with Ireland and Italy we found an association between occupational exposure to silica and ALS risk. Results have to be validated as this is the first time such an association has been described. We also showed that, compared to parents of controls, parents of patients died less frequently from a cardiovascular disease. An increased ALS risk, and fewer cardiovascular risk factors could be the result of a specific pathway, modified by genetic predisposition, possibly combined with exogenous risk factors, such as physical activity. It has long been thought that ALS patients are ‘fitter’ than controls regarding physical activity, as we also found in our study. However, we found more frequent use of cholesterol lowering and antihypertensive medication among patients, but three years prior to study participation this effect was reversed. Lastly, we found no association between a Borrelia burgdorferi infection or gluten sensitivity and ALS risk. Therefore, we do not support the inclusion of routine testing for these antibodies in the diagnostic workup in patients with classical ALS. Also, we consider a role for a gluten-free diet in the ALS treatment unlikely.
Keywords: Amyotrophic lateral sclerosis; risk factors; epidemiology